Colonial migrants at the heart of empire : Puerto Rican workers on U.S. farms - García-Colón, Ismael (American crossroads, 2020)
"Colonial Migrants at the Heart of Empire is the first comprehensive look at the experiences of Puerto Rican migrant workers in mainland US agriculture in the twentieth century. Ismael García-Colón investigates the origins, establishment, and development of the Puerto Rico Farm Labor Program by the government of Puerto Rico in 1947, which placed hundreds of thousands of migrant workers on US farms and fostered the emergence of many stateside Puerto Rican communities. Colonial Migrants is both a labor history and an ethnography of the experience of migrant farm workers in US rural communities, evoking the violence, fieldwork, food, lodging, surveillance, and coercion that Puerto Ricans encountered on farms. One of the first books to explore the particular prejudice and racism faced by island farmworkers as they interacted with US rural communities, it reveals the dual status of Puerto Ricans as both US citizens and racialized "foreign others." Despite the complexities of navigating this dual status, many workers ultimately stayed in these communities and contributed to the demographic and ethnic changes of rural America"--